INTEGRASI YURIDIS NORMATIF DAN PSIKOLOGIS UNTUK MERAIH CINTA DAN BAHAGIA DALAM UNDANG-UNDANG PERKAWINAN DI INDONESIA - Nafisah, Durotun (ADHKI: JOURNAL OF ISLAMIC FAMILY LAW, 2019)
The Marriage Law in Indonesia (UUP) is a positive legal rule in building a family. The UUP for example states that the purpose of marriage is to form a happy family, while the obligations of a husband and wife are to love, respect, respect and be loyal. Happiness, love, respect and loyalty are part of the psychological domain that cannot be achieved by merely reading normative juridical rules. Therefore a psychology study is needed to study the UUP. In addition to the psychological aspects, it is also important to study the UUP with a normative approach to see whether the UUP elaborates the normative values ​​of the Qur'an as a source of Islamic teachings. The background of this paper is compiled with the aim of explaining the manifestations of psychological aspects formulated in the UUP so that it can be a reference for implementation in building families and analyzing the normative values ​​of the Qur'an absorbed by the UUP. Therefore this UUP study was conducted with an integrated approach to normative and psychological juridical. This study also aims to develop family law with an integrative juridical psychological approach. The primary data sources used are the book of the Qur'aan by Quraysh Shihab, UUP and the book Motivation and Personality which examines happy psychology by Abraham H. Maslow and Triagular Theori of Love which discusses the theory of love in psychological perspective by Robert. J Steinberg as well as secondary sources related to research. The results of this study indicate that forming a happy family as a marriage goal is in harmony with Q.S. ar-Rum (30): 21. While in a psychological perspective marital happiness can be achieved by a husband and wife can achieve if fulfilled the five basic human needs (hierarchy of needs) in humanistic psychology namely: physiological, security, social, appreciation and self-actualization needs. While husband and wife love is manifested in three aspects, namely attachment, caring and intimacy.